Association between comprehensive geriatric assessment and Days Alive and Out of Hospital at 30 Days After Cardiac Surgery in Older Patients - Seo Hee Ko; Jae-Kwang Shim; Eun Hwa Kim; Jong Wook Song; Sarah Soh; Young-Lan Kwak (The Journal of Nutrition, Health and Aging)
Objectives: To investigate the association of comprehensive geriatric assessment (related to diverse aspects of frailty) with postoperative recovery as measured by days alive and out of the hospital at 30 days (DAOH30) in older patients undergoing cardiac surgery. Design: Retrospective observational study using data retrieved from a prospective registry. Setting: Single tertiary hospital in South Korea. Participants: A total of 437 patients aged ≥65 years who underwent cardiac surgery between March 2021 and October 2022 were included. Measurements: Comprehensive geriatric assessment included subjective evaluations of functional frailty (cognitive, emotional, and physical aspects) and objective measurements of malnutrition and anaemia. DAOH30 was analysed using multivariable quantile regression to evaluate its association with these three domains. Results: In the entire cohort (median age 72 years; median DAOH30, 19 days), 85.1% of participants had functional frailty, 9.8% had malnutrition, and 45.8% had anaemia. Older age, cognitive dysfunction, emotional dysregulation, physical decline, malnutrition, and anaemia were associated with shorter DAOH30 (all p < 0.05). In multivariable analysis, malnutrition had the strongest impact, reducing DAOH30 by 6.0 days (95% confidence interval [CI]: −11.103 to −0.263), followed by anaemia (1.2 days, 95% CI: −2.199 to −0.148) and functional frailty (1.0 days, 95% CI: −1.677 to −0.171). Individual components of functional frailty did not retain an independently significant relationship with DAOH30 after adjustment for confounders. Conclusion: Comprehensive geriatric assessment, incorporating functional frailty, malnutrition, and anaemia, demonstrated a significant association with DAOH30 in older patients undergoing cardiac surgery. Among the assessed aspects, malnutrition showed the strongest association, which may underscore the importance of targeted nutritional interventions to improve outcomes in this patient population.